Shades of Brown: A Model for Thermogenic Fat - Dempersmier, Jon; Sul, Hei Sook (Frontiers in Endocrinology, 2015)
Brown adipose tissue (BAT) is specialized to burn fuels to perform thermogenesis in defense of body temperature against cold. Recent discovery of metabolically active and relevant amounts of BAT in adult humans have made it a potentially attractive target for development of anti-obesity therapeutics. There are two types of brown adipocytes: classical brown adipocytes as well as brown adipocyte-like cells, so called beige/brite cells, that arise in white adipose tissue in response to cold and hormonal stimuli. These cells may derive from distinct origins, and while functionally similar, have different gene signatures. Here, we highlight recent advances in the understanding of brown and beige/brite adipocytes as well as transcriptional regulation for development and function of murine brown and beige/brite adipocytes focusing on EBF2, IRF4 and ZFP516, in addition to PRDM16 as a coregulator. We also discuss hormonal regulation of brown and beige/brite adipocytes including several factors secreted from various tissues, including BMP7, FGF21 and irisin, as well as those from BAT itself, such as Nrg4 and adenosine.